Antibacterial activity and toxicity of the ethanolic extract of Eugenia Uniflora L. Leaves On Pseudomonas Aeruginosa - Bobadilla, Fernando Javier (2018)
Pseudomonas aeruginosa is one of the main causes of nosocomial infections worldwide, with great potential for multi-resistance development. The World Health Organization (WHO) considers the antimicrobial resistance as an emerging public health problem that makes new therapies an extremely urgent issue. The aim of this work was to study the antibacterial capacity of the ethanolic extract of Eugenia uniflora L. leaves on Pseudomonas aeruginosa, its possible synergistic action with commercial antibiotics and to carry out general toxicity tests using the crustacean Artemia salina. The extract had a Minimum Inhibitory Dose (MID) of 0.5 mg.disc-1. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericide Concentration (MBC) for P. aeruginosa PAO1 were 1.33 mg.ml-1 and 13.33 mg.ml-1. For the clinical isolations were 0.83 mg.ml-1 and 8.33 mg.ml-1. The MBC/MIC ratio (MICI) qualified the action of the extract as bacteriostatic. The Time-killing curve showed that the total loss of viability of the bacteria occurs at 24 h to 16 mg.ml-1 and at 8 h to 32 mg.ml-1. The combination of meropenem with the extract results in a decrease in its inhibitory action on P. aeruginosa PAO1. Meanwhile, the combination with piperacycline or ceftazidime produces a synergistic action. For ciprofloxacin, amicacin and colistin the combination is indifferent. The LC50 obtained using A. salina was 0.61 mg.ml-1; indicating that the extract has a moderate toxicity. These results suggest that this species would be a potential source of antimicrobial agents to be applied in the treatment of infections caused by P. aeruginosa.